PENGARUH STATUS SOSIAL EKONOMI ORANGTUA, LITERASI KEUANGAN, DAN KONTROL DIRI TERHADAP MANAJEMEN KEUANGAN PADA MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS GUNUNG LEUSER ACEH - Rila Maufira; Rahmat Arfan; Rina Malahayati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Abstract Education plays an important role in the formation of financial management, both informal education in the family environment and formal education in the tertiary environment. Within the family environment, the level of financial management is determined by the role of parents in providing support in the form of financial education in the family. Financial management education in the family is influenced by the socioeconomic status of the parents. Differences in the socioeconomic status of parents make a big difference in parenting. Children are conditioned by socio-economic class which influences their knowledge and behavior. Learning in tertiary institutions plays an important role in the process of establishing student financial management. Appropriate and directed learning will help students have the ability to understand, assess, and act in their financial interests. High levels of financial knowledge are positively correlated with higher levels of income and savings. By having financial literacy, students are able to make decisions for their lives and accept responsibility for their own actions (Danes in Jorgensen, 2007). Financial literacy is closely related to financial management where the higher a person's level of financial literacy, the better his financial management. Personal financial management is an application of the concept of financial management at the individual level. Financial management, which includes financial planning, management and control activities, is very important to achieve financial prosperity. Planning activities include activities to plan the allocation of income earned will be used for anything. Parents' socioeconomic status is one of the external factors that influence student financial management. Parents' socioeconomic status includes parents' education level, parents' occupation, and parents' income. Financial management carried out by students is in the form of management in controlling personal financial expenses which are carried out continuously. When students find it difficult to control expenses that are made continuously and are unlimited in number, then it shows that these students have poor financial management. Therefore, it is important to conduct this research to determine the effect of parents' socio-economic status, the effect of financial literacy, and the effect of self-control on the financial management of students of management at the Faculty of Economics, University of Gunung Leuser Aceh. Keywords: Financial management, socioeconomic status.